2010
DOI: 10.1002/glia.21110
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin: Correlation with phagocytosis by brain macrophages in a rat model of stroke

Abstract: Osteopontin (OPN) is an adhesive glycoprotein linked to a variety of pathophysiological processes. We investigated whether OPN might act as an opsonin in the diseased brain by studying the postischemic expression and localization of OPN mRNA and protein in a rat model of ischemic stroke. In addition, we characterized the subcellular localization of OPN protein in the ischemic brain core. Induction of OPN mRNA occurred in activated microglia/macrophages in the ischemic core on days 3-7 after reperfusion and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 36 publications
10
55
0
Order By: Relevance
“…In contrast, we found that the proliferation of primary rat microglia was unaffected by OPN, as measured by both absolute cells numbers as well as by RT-qPCR for Ki67, suggesting that those effects depend on cell type, species, and potentially also culture conditions. Likewise, OPN was reported to enhance the phagocytic activity of porcine microglia (Tambuyzer, Casteleyn, 2012) and rat macrophages/microglia after experimental stroke in vivo (Shin et al , 2011), while we found no influence of OPN on phagocytic activity of primary rat microglia in vitro. While OPN is a known chemoattractant for macrophages (Lund et al , 2013), it did not exert a chemotactic effect on our primary rat microglia.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…In contrast, we found that the proliferation of primary rat microglia was unaffected by OPN, as measured by both absolute cells numbers as well as by RT-qPCR for Ki67, suggesting that those effects depend on cell type, species, and potentially also culture conditions. Likewise, OPN was reported to enhance the phagocytic activity of porcine microglia (Tambuyzer, Casteleyn, 2012) and rat macrophages/microglia after experimental stroke in vivo (Shin et al , 2011), while we found no influence of OPN on phagocytic activity of primary rat microglia in vitro. While OPN is a known chemoattractant for macrophages (Lund et al , 2013), it did not exert a chemotactic effect on our primary rat microglia.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…Since OPN is elevated under conditions of inflammation (Patarca et al, 1989; Hwang et al, 1994; Weber and Cantor, 1996; Chabas et al, 2001), and can direct the migration of macrophages and microglia to sites of brain injury (Ellison et al, 1998; Shin et al, 2011; Hashimoto et al, 2003), it is possible that manipulation of inflammation will affect OPN role in these processes during early synaptogenesis. To test this possibility, we used the tricyclic antibiotic minocycline (delivered acutely at 30 min and 6 h post-UEC lesion) to attenuate inflammatory response, as well as reduce microglial activation (Yrjanheikki et al, 1998; Yrjanheikki et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…OPN fragments can also stimulate microglial activation, shifting the cells into a pro-inflammatory M1 state, as well as induce macrophage proliferation to facilitate phagocytosis (Tambuyzer et al, 2012). OPN producing macrophages participate in debris clearance after stroke (Shin et al, 2011) and CNS demyelination (Zhao et al, 2008). Acutely, OPN can stimulate reactivity of astrocytes at sites of deafferentation, enhancing MMP targeting of ECM proteins like agrin, phosphacan and N-cadherin, whose lysis permits deconstruction of injured synapses prior their reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…We recently suggested that OPN is involved in phagocytosis of fragmented cell debris by macrophages in response to cerebral ischemia (Shin et al 2011) and that calcium precipitation in cell debris facilitates local binding of OPN, leading to OPN-mediated phagocytosis (Shin et al 2012). This proposal was supported by the present finding that most OPN deposits were encompassed by brain macrophages at 12 weeks, the latest time point examined (Fig.…”
Section: Discussionmentioning
confidence: 99%